Analysis of Performance Effectiveness of Production Team in the Fashion Retail Business Using the Team Metrics - Yaqin, Nadine; Islaha, Shafia (Universitas Pendidikan Indonesia, 2024)
Fashion retail sector is one of the largest sources of employment in Indonesia and also shows the tight business competition in the fashion retail sector. As a company that carries the concept of fast fashion, the production team at PT X is one of the divisions that has a crucial role in its business process. The purpose of this study is to determine the efficacy of PT X's production division's performance using the team metrics approach developed by Woodcock and Francis. The Team Blockage Questionnaire and the Internal-Process-Output (IPO) style of interviewing were employed in this study. The assessment results show that the team still has to improve in a few areas in order to perform more effectively at work. The significant variable in understanding why the team's performance is not as effective as it should be is leadership. Interventions are therefore needed to improve these crucial areas for the affected employees as well as for other division and management members.